2021
DOI: 10.3390/ma15010030
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Evolution of sp2 Hybrid Conjugate Structure of Polyacrylonitrile Precursor during Stabilization

Abstract: The generated sp2 hybrid conjugate structure of a C atom, which resulted from the chemical reaction affected by temperature and time, is an effective six-membered ring planar structure of the final carbon fiber. This kind of hybrid conjugate structure determined the formation of the final structure and mechanical properties of carbon fiber. In this paper, the formation and evolution of sp2 hybrid conjugated structures of PAN precursor during thermal stabilization were investigated by Raman, UV-vis and 13C-NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This absorption band was assigned with the n- π* transitions of C-O and C-N groups in the polymeric matrix. 76 From the spectrum of the same sample (Figure S1(a)), it can show that weak bands at wavelength of ˜ 247 nm and ˜ 60 nm represented a π- π* transition and n- π* transition of C=O and C=C bonds, 48,77 respectively. Whitford et al 48 reported that an absorption peak in the ultraviolet region of 265–275 nm with varying intensity attributed to the PAN chromophore.…”
Section: Resultsmentioning
confidence: 99%
“…This absorption band was assigned with the n- π* transitions of C-O and C-N groups in the polymeric matrix. 76 From the spectrum of the same sample (Figure S1(a)), it can show that weak bands at wavelength of ˜ 247 nm and ˜ 60 nm represented a π- π* transition and n- π* transition of C=O and C=C bonds, 48,77 respectively. Whitford et al 48 reported that an absorption peak in the ultraviolet region of 265–275 nm with varying intensity attributed to the PAN chromophore.…”
Section: Resultsmentioning
confidence: 99%
“…The longer the absorption peak is, the larger the electron delocalization structure the CDs may have, which is consistent with the phenomenon that the fluorescence of the CDs changes from blue to red. 45,46 In Fig. 1B, the fluorescence of CDs separated by different polar solvents ranges from 439 nm to 615 nm.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Relevant scholars have put forward that the characteristic structure formed during the pre-oxidation process included C=C, C=N and aromatic heterocyclic conjugated groups, which could be characterized and analyzed by UV-vis spectroscopy [27,28]. This was because the absorption wavelength of UV-vis absorption spectrum was usually in the range of 200-800 nm, and it could significantly characterize the n-π * and π-π * orbital transitions of unsaturated bond conjugated systems.…”
Section: Introductionmentioning
confidence: 99%